Alteration in Lipid and Protein Profiles of Ovarian Cancer: Similarity to Breast Cancer. Issue 9 (1st November 2011) - Kang, Sokbom; Lee, Aera; Park, Young Seung; Lee, Seok Cheol; Park, Sang Yoon; Han, Sang Yun; Kim, Kwang Pyo; Kim, Young Hwan; Yoo, Chong Woo; Kim, Hark Kyun
Abstract : Abstract: This study was undertaken to evaluate protein and lipid profiles of ovarian cancer tissue samples. Twenty-three frozen ovarian cancer samples and 6 adjacent normal samples were analyzed using histology-directed, matrix-assisted laser desorption/ionization mass spectrometry. Sinapinic acid and 2, 5-dihydroxybenzoic acid/α-cyano-4-hydroxycinnamic acid were manually deposited on areas of each tissue section enriched in epithelial cells to identify protein and lipid profiles respectively, and mass spectra were acquired using a matrix-assisted laser desorption/ionization–time of flight instrument. Protein and lipid profiles classify 11 cancer and 3 adjacent normal samples in 100 random test sets with 92.9% median accuracy. Phosphatidylcholines {32:3} [M + Na] + ( m / z = 750.66), {34:1} [M + K] + ( m / z = 798.60), and {36:2} [M + K] + ( m / z = 824.56) were found to be increased in ovarian cancer. Interestingly, breast cancer–associated changes in lipid and protein profiles were also found in ovarian cancer. Thus, protein and lipid profiles accurately distinguish ovarian cancer from adjacent normal tissue samples. Common cancer-associated alterations in lipid and protein profiles were identified between ovarian and breast cancers.